Deciphering Sociopolitical Context of Samantha Lucille Tancontian’s Buhay Frontliner in the Covid-19 Era - Sabonsolin, John Cavin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The covid- 19 pandemic changes our society's lifestyle, culture, and issues. The unprecedented event brought people to adjust in their lives as the government also changed its implementation of protocols and guidelines to be safe during the pandemic. This literary research study assumes that Samantha Lucille Tancontian's Buhay Frontliner, written during the intense lockdown and early pandemic, reveals the contemporary sociopolitical context. Using critical discourse analysis, the researcher explores the local colors, plot, and themes that reveal contemporary sociopolitical context. The researcher anchors the readers' response theory on analyzing the fictional short story. Results indicate that the short story shows contemporary sociopolitical issues. The study confirms that the short story "Buhay Frontliners" has contemporary sociopolitical problems embedded in its literary elements.